(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Competency Based Medical Education (CBME) and Curriculum Implementation Support Program (CISP) are gaining a lot of momentum in India. Lecture still remains as a very important large group teaching method. Attendance of the students was seen to be reduced in weekend lectures. The primary objective of this research work was to estimate the understanding of learning objectives of the previous weekend lecture; and to get the students’ feedback on ‘status of attendance’, ‘relevance of weekend lectures’, ‘acceptance as adult learners’ and ‘marking proxy attendance in lectures’. The secondary objective was to find the association of the answers with that of ‘status of attendance’. The tertiary objective was to check if any association existed between students’ responses of ‘relevance of weekend lectures’, ‘marking of proxy attendance in lectures’ and ‘acceptance as adult learners’. A feedback questionnaire tool post validation was conducted unannounced following the weekend lecture and students voluntarily participated in the same – sample size was 82. The students who had attended the lecture had given the maximum number of correct responses. The largest group of responses were ‘not answered’ and they belong to those who had not attended the lecture. All these interpretations of associations were found to be highly significant statistically - p < 0.001. There was an association between responses of ‘acceptance as adult learners’ with that of ‘marking proxy attendance in lectures (as bad attitude)’ - p < 0.049.